Muhammad Ali : champion of the world - Winter, Jonah, 1962- (Schwartz & Wade Books, 2007)
Provides a profile of this legendary and flamboyant boxer and the complicated life he led, from changing his religion and his name to dodging the draft during the Vietnam Era and fighting his way to regain a stripped title.